European monetary integration - Coffey, Peter; Presley, John R. (London : Macmillan; St. Martin's Press, 1971)
This book provides the history of decision to establish European monetary integration, and examines both the theoretical side of monetary integration and the possibility of the evolution of European capital market.
Includes index.
Includes bibliographical references.
usc 18/10/2018
Loans
Keywords: Money; Currency question; Europe--European Economic Community countries